Effect of sea buckthorn (Hippophae rhamnoides) on kidney and testicular damage, sperm quality and expression of Irisin and Asprosin in Streptozotocin-Induced diabetic rats - Pekince-Özöner, Merve; Timurkaan, Sema; Gür, Fatih Mehmet; Tarakçi-Gençer, Berrin; Eröksüz, Hatice; Güngör, İbrahim Halil (Universidad del Zulia, Facultad de Ciencias Veterinarias, 2025)
In recent years, many antioxidants have been used against hyperglycemia and oxidative damage in diabetes. The purpose of this study is to investigate the protective effects of Sea buckthorn (Hippophae rhamnoides) against adverse effects of diabetes on testicular and renal tissues. A total of 39 male Sprague-Dawley rats were assigned to 5 groups as follows: control, citrate, SBT, diabetes, and diabetes+SBT. Diabetes induction was made by streptozotocin (50 mg/kg intraperitonally) to diabetes and diabetes+SBT group. SBT oil was administered to SBT and diabetes+SBT group (50mg/kg/48h by oral gavage). At the end of study, testicular and kidney samples for histochemical and immunohistochemical examinations, serum samples for biochemical examinations and sperm samples for spermatogenic examinations were collected. The results of the analysis showed that SBT reduced body weight loss and lowered blood glucose levels by reducing the harmful effects of diabetes-induced oxidative stress. When serum TAS and TOS levels were evaluated, it was determined that TAS level was the highest in the SBT group and TAS level increased in the diabetes + SBT group compared to diabetes and the other groups. While TOS level increased in the diabetes group, it decreased in the diabetes+SBT group. SBT also increased sperm density and motility and reduced total abnormality (head-tail) in diabetic rats. In SBT-treated diabetic rats, histopathological changes during the course of diabetes significantly reduced. In addition, decreased irisin expression in renal tissue and decreased irisin and asprosin expression in testicular tissue in the diabetes group were significantly normalized in the diabetes+SBT group. In this study, it was found that the application of SBT oil significantly prevented hyperglycemia and oxidative stress in diabetes, and protected testicular and renal tissues from the functional and histopathological changes in these organs caused by hyperglycemia and oxidative stress in diabetic animals. These results showed that SBT oil was an effective nutritional supplement that can be used to protect against the adverse effects of diabetes. © (2025), (Revista Cientifica de la Facultad de Veterinaria). All rights reserved.
Efecto del espino amarillo (Hippophae Rhamnoides) sobre el daño renal y testicular, la calidad del esperma y la expresión de Irisina y Asprosina en ratas diabéticas inducidas por Estreptozotocina
Keywords: Asprosin; Asprosina; calidad del esperma; diabetes; diabetes; espino amarillo; estrés oxidativo; Irisin; Irisina; oxidative Stress; sea buckthorn; sperm quality